50th Jubilee Winter School on Wave and Quantum Acoustics XLIXth Winter School on Environmental Acoustics and Vibroacoustics Szczyrk, Poland, 28 February – 3/4 March, 2022 (Archives of Acoustics, 2022)
On behalf of Upper Silesian Division of the Polish Acoustical Society (main organizer) and Committee of Acoustics of the Polish Academy of Sciences (coorganizers) we are pleased to announce that according to many years of tradition the above-mentioned Conferences known as “Winter Schools” have been organized and carried out. 50th Jubilee Winter School on Wave and Quantum Acoustics constituted platforms for sharing the results and achievements obtained in different branches of physical acoustics (e.g. molecular acoustics, relaxation processes, quantum acoustics, acousto-optics, magnetoacoustics, photoacoustics, acoustics of solid state, acoustic emission etc.). Conference consisted of 17th Workshop on Acoustoelectronics and 17th Workshop on Molecular Acoustics, Relaxation and Calorimetric Methods. XLVIXth Winter School on Environmental Acoustics and Vibroacoustics was the forum for all environmental and vibroacoustics fields. Particularly it concerned traffic noise, vibroacoustics of machines, room acoustics, building acoustics, noise protection and similar problems. Celebrations of the “Golden Jubilee included: • Jubilee Session with plenary lecture “The Golden Jubilee of the 50th Winter School on Wave and Quantum Acoustics – historical reminiscences” presented by prof. Tadeusz Pustelny and numerous touching addresses, • Special Session “50 years have gone by ... – an evening of remembrance” conducted by prof. Marzena Dzida; it was a very nice session, without time restrictions as to presentations and discussions and the real duration of this session was twice as large as planned. Finally, 52 people participated within Conferences presenting 44 lectures, reports and posters. In this issue one can find abstracts of some lectures and posters, which were presented during the Conferences. We are pleased to announce that on 27 February – 2/3 March, 2023, we will organize the next “Winter Schools” containing the Lth Jubilee Winter School on Environmental Acoustics and Vibroacoustics and 51st Winter School onWave and Quantum Acoustics. Thus, just now we invite you to participate in this “Golden Jubilee” Conference. We would like to invite scientific centres and groups to cooperate in organizing workshops on the subjects of their interests related to the theme of the Conference. Further information about Conferences is available on our website https://ogpta.pl/index.php/en/